Community Based Social Therapy Approaches for Strengthening Local Governancein Kaski District, Nepal - Paudel, Mohan Kumar; Baral, Ramchandra; Panta, Saroj Raj; Panta, Suveksha (International Research Journal of MMC, 2026)
Social therapy is known as an intersectional method for social audit within local governance. It is the process of revitalizing of community consciousness and accountability by seeding, feeding and bridging ethical governance through social therapy interventions. Social therapy affects questioning power of citizens and enhance inclusivity and responsiveness among authentic unit of government. The study based on 72 wards of Kaski District, Nepal. The major objective of this study was to examine the government officials' perceptions regarding elected representatives' decision-making dynamism, civic complaint facilities and hearings at the local levels. It applied community intervention and social prescribing theories to address governance challenges such as limited participation, weak accountability and service delivery gaps. It advocates mobilizing social therapy to rebuild civic trust, amplify citizen voice and foster collaborative governance. A descriptive and analytical study design grounded in a quantitative approach was employed in this study. A structured survey was conducted in line with cluster sampling of 82 government authorities from five local government units of the district. Data were collected with the support of structured questionnaires. The findings indicate that accessible civic complaint systems and frequent public hearings interventions through dialogic engagement and community-based participatory practices offer a transformative pathway for strengthening trust, accountability and civic engagement. This study may be useful for local bodies and future researchers.